Occurrence of G10P[11] Genotype of Group A Bovine Rotavirus in Diarrheic Calves from in and around Navsari, Gujarat - Makwana, Pushpa M; Kalyani, Irsadullahkhan H; Desai, Dhruv N; Vihol, Priti D; Patel, Jignesh M; Solanki, Jayesh B; Patel , Dharmesh R (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
A study was undertaken to ascertain genotypic characterization of bovine group A rotavirus circulating in the Navsari region of Gujarat state. Total 157 diarrheic fecal samples were collected from bovine calves of organized farms and locally at village level from Navsari region. All the samples were initially screened by RNA-PAGE and RT-PCR followed by characterization by sequencing and G-P typing. The study revealed 10 (6.36%) samples positive by RNA-PAGE, while 16 (10.19%) samples were positive by VP4, VP6 and VP7 gene based RT-PCR. From these positive samples, representative samples were sequenced for complete coverage of VP4, VP6, and VP7 genes followed by P and G typing on the basis of VP4 and VP7 sequence results, respectively. All the sequenced samples revealed G10 and P[11] types, showing a G10P[11] combination significantly prevailing in the bovine calves. Phylogenetic analysis of VP4, VP6, and VP7 genes was performed to determine the cross-species transmission dynamics and regional diversity, which showed similarity with other isolates circulating in India. Our findings suggested that a zoonotic potential genotype G10P[11] is the most circulating genotypes of Rotavirus A in bovine calves from Navsari region of Gujarat, India.